Viajantes do tempo: imigrantes-refugiadas, saúde mental, cultura e racismo na cidade de São Paulo - Branco-Pereira, Alexandre (Universidade Federal de São Carlos, 2019)
This is an ethnography of immigrant-refugees that live or lived in the city of São Paulo which intends to describe the experiences of immigration-refuge in the city. Addressing the processes of consideration of immigration-refuge as a monolithic block, peripheralization and access or not to the city, the experience of racism and the diverse and dynamic hierarchies of alterities formulated by mechanisms of reception and integration / assimilation architected by the State and by supra-state organisms, I argue that unassimilable immigrants-refugees in Brazil go through processes designed to carry out a "temporal update" of cultures and minds considered pre-modern. Unassimilable, because are included by exclusion, are therefore time travelers, originating from the past, not cohabiting present time with modern ones. The perspective from mental health services specialized in immigrants-refugees becomes a privileged locus for apprehending and examining such logics. I also argue that the logic imposed by humanitarianism-gift, a relationship of reciprocity not necessarily altruistic between welfare services and immigrants-refugees, becomes a place of exchanges and dialogues only imagined, projecting on the latters an avocality that, coupled with the equivalences made between them and deafs, demonstrate that deafness in this context is more an incapacity of being heard than to hear. In addition, it shows that the curse of tolerance (Stengers, 2011) divides the world, under the perspectives of reception and integration / assimilation services, between those who believe and those who know, a logic that goes transversally through the mechanisms of "temporal updating" from immigrantsrefugees’ (and any others considered pre-modern) cultures and minds. Finally, I describe how the settlement of this scenario by anthropologists and anthropology can take place, advocating in favor of upholding anthropology as a tool for the production of data and care and, above all, for diplomatic mediation between worlds
Viajantes del tiempo: inmigrantes-refugiadas, salud mental, cultura y racismo en la ciudad de São Paulo
Time travelers: immigrants-refugees, mental health, culture and racism in the city of São Paulo
Keywords: Imigrantes; Refugiados; Refugiadas; Saúde mental; Racismo; Temporalidades; São Paulo; Immigrants; Refugees; Mental health; Racism; Temporalities; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA